Steel City Readers Reading for Pleasure in Sheffield, 1925-1955 - Grover, Mary (Liverpool University Press, 2023)
Steel City Readers makes available, and interprets in detail, a large body of new evidence about past cultures and communities of reading. Its distinctive method is to listen to readers' own voices, rather than theorising about them as an undifferentiated group. Its cogent and engaging structure traces reading journeys from childhood into education and adulthood, and attends to settings from home to school to library. It has a distinctive focus on reading for pleasure and its framework of argument situates that type of reading in relation to dimensions of gender and class. It is grounded in place, and particularly in the context of a specific industrial city: Sheffield. The men and women featured in the book, coming to adulthood in the 1930s and 1940s, rarely regarded reading as a means of self-improvement. It was more usually a compulsive and intensely pleasurable private activity.